Improving Students’ Speaking Ability by Using YouTube Application at Madrasah Aliyah Kalosi - Ardianto Ardianto; Kisman Salija; Amra Ariyani (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this study was to determine whether the use of YouTube application videos in teaching speaking improve the students’ speaking ability. Pre-experimental design is a method used by researchers with one group class pre-test and post-test. The population is class X Madrasah Aliyah students in the 2022/2023 academic year. Samples were taken using cluster random sampling technique consisting of 32 students. The instrument of this research is speaking test which is given as pre-test and post-test. The results of this study prove that there is a significant difference between students' scores before treatment and students' scores after treatment. Students' speaking ability after the application of the YouTube application video or better than before the use of the YouTube application. This can be seen from the average score, the students' pre-test average score (61.97) and lower than the post-test average (82.47). The significance value of this study (0.000) is smaller than the significant level (0.05). It can be concluded that the use of the YouTube application to improve the students’ speaking ability in terms of Vocabulary, Pronunciation, Grammar in the tenth grade of Madrasah Aliyah Kalosi.